Priority Strategy For Improving Dam Operation and Maintenance Performance (Cacaban Dam Case Study) - Ary Aprianto (Publikasi Indonesia, 2024)
Dam operation and maintenance activities are critical, so the dam usually works and provides benefits according to plan. Over time, the performance of the Cacaban Dam has decreased significantly. The physical condition of the main building, supporting buildings, and instruments have experienced damage, which could pose a risk to the dam's safety. The main objective of this research is to determine priority strategies for improving operations and maintenance of the Cacaban Dam. Determining priority strategies for improving operations and maintenance in this research uses the DSS (Decision Support System) method with SWOT (Strength, Weakness, Opportunity, and Threat) and QSPM (Quantitative techniques Strategic Planning Matrix). Based on the SWOT analysis results, the resulting strategy is the Diversity Strategy, meaning that the Cacaban Dam is in good internal condition. In contrast, the external condition is not good. The proposed strategy is to minimize external threats/threats with strategic priorities referring to the scoring results using the QSPM method. Meanwhile, from the results of the dam performance assessment, Cacaban Dam obtained an average performance score of 3.45, considered adequate performance. However, if you look at several items of poor performance, there are two items, namely reservoir condition and border and greenbelt conditions, which have poor performance. There are seven components, namely intake buildings, spillway buildings, support hills, dam services, emergency action plans, instrumentation, and surrounding communities, whose performance is quite close to the deficient limit and has the potential for performance to decline. Extra handling is needed to restore the performance of dams and reservoirs.